Contributions of MNCs to poverty alleviation through CSR programs: Odisha Perspective - Gangwar, Anubhav Singh (The journal of contemporary issues in business and government, 2023)
Purpose – This study investigates how Multinational Corporations' (MNCs') CSR initiatives have helped to reduce poverty in Odisha, India. Design/methodology/approach – By means of consulting annual reports, websites, and publications for quantitative information, we have used a mixed-method approach to gather qualitative data by interviewing Managers of five MNCs. The average contribution of sample MNCs to CSR programmes is only 0.52% of profits after taxes, with ranges from 2.96 to 0.15%. Findings – Results showed that MNCs' Corporate Social Responsibility (CSR) programmes had little impact on reducing poverty in Odisha District. According to the report, the majority of MNCs do not give as much as they are able to and do not have a policy of giving a decent amount of their profits to CSR with a focus on reducing poverty. Research limitations/implications – The current study is limited to studying the contributions of MNCs in poverty alleviation by means of only their CSR programs and also the current study is confined to the state of Odisha. Thus, leaving future scope for budding researchers to identify the impact of such programs with respect to other regions and also other activities that may contribute in poverty alleviation. Practical implications - According to the study, in order to accelerate the movement towards poverty alleviation for a joyful, prosperous, and forward-thinking Odisha, the Government of Odisha must act sincerely and purposefully to encourage MNCs to actively participate in CSR programmes that prove to be beneficial for reducing poverty by providing the necessary policy framework and motivating supports. Originality/value – This paper is one of a few attempts to identify the contributions of MNCs in poverty alleviation specifically in the state of Odisha in India, by means of CSR programs in particular.